Store Atmosphere, Store Location, E-Reviews, dan Consumer Purchase Intention - Humairoh Humairoh; Mohammad Annas; Muhammad Rifqi (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study was to determine the effect of store atmosphere, store location, and e-review on consumer purchase intention. The type of research used is quantitative research. The sample used in this study amounted to 96 respondents who were calculated using the Lemeshow formula with a non-probability sampling technique, namely consumers who made purchases at the Kopituh coffee shop. Data were taken using a questionnaire instrument with a survey method using google Forms and analyzed using SPSS software version 26. The results showed that part there was a positive and significant influence on the store atmosphere variable on consumer purchase intention with a t count of 11,042, store location have a positive and significant effect with a t count of 10,717, and e-review had a positive and significant effect on consumer purchase intention with a t count of 10,134, and. Then the store atmosphere, store location, and e-review, variables together or simultaneously have a significant effect of 68,060. While the results of the coefficient of determination (R2) obtained a value of 0.689, meaning that the overall store atmosphere, e-review, and store location variables can explain the contribution of 68.90% to consumer purchase intention, while the remaining 31.10% is explained by other variables that not used in this stud